Cholinergic transmission from the basal forebrain modulates social memory in male mice - Kljakic, Ornela; Al-Onaizi, Mohammed; Janíčková, Helena; Chen, Kevin S; Guzman, Monica S; Prado, Marco A M; Prado, Vania F (The European journal of neuroscience, 2021)
Disruptions in social behaviour are prevalent in many neuropsychiatric disorders such as schizophrenia, bipolar disorder and autism spectrum disorders. However, the underlying neurochemical regulation of social behaviour is still not well understood. The central cholinergic system has been proposed to contribute to the regulation of social behaviour. For instance, decreased global levels of acetylcholine release in the brain leads to decreased social interaction and an impairment of social memory in mice. Nonetheless, it has been difficult to ascertain the specific brain areas where cholinergic signalling influences social preference and social memory. In this study, we investigated the impact of different forebrain cholinergic regions on social behaviour by examining mouse lines that differ in their regional expression level of the vesicular acetylcholine transporter-the protein that regulates acetylcholine secretion. We found that when cholinergic signalling is highly disrupted in the striatum, hippocampus, cortex and amygdala mice have intact social preference but are impaired in social memory, as they cannot remember a familiar conspecific nor recognize a novel one. A similar pattern emerges when acetylcholine release is disrupted mainly in the striatum, cortex, and amygdala; however, the ability to recognize novel conspecifics is retained. In contrast, cholinergic signalling of the striatum and amygdala does not appear to significantly contribute to the modulation of social memory and social preference. Furthermore, we demonstrated that increasing global cholinergic tone does not increase social behaviours. Together, these data suggest that cholinergic transmission from the hippocampus and cortex are important for regulating social memory.
Keywords: pars basalis telencephali; acetylcholin; forebrain; Acetylcholine; hipokampus; vezikulární transportní proteiny acetylcholinu; acetylcholine; mužské pohlaví; Mice; autism; Cholinergic Agents; Animals; cholinergní látky; Hippocampus; myši; social memory; Basal Forebrain; Vesicular Acetylcholine Transport Proteins; schizophrenia; Male; zvířata